Estimating the Effects of the Minimum Wage Using the Introduction of Indexation - Daiji Kawaguchi; Yuko Mori (Institute of Labor Economics (IZA), 2021)
We examine the impacts of the minimum wage on employment using the minimum-wage hike induced by the introduction of indexation of the local minimum wage to the local cost of living. The revision of the Minimum Wage Act in 2007 of Japan essentially required the government to set the minimum wage indexed to the local cost of living, with a five-year moratorium period. The government subsequently increased the minimum wage in areas where the cost of living was high relative to the local minimum wage. Allowing for different trends in labor-market outcomes across regions in the pre-treatment period, we find that the minimum-wage hike raised the wages of low-wage workers, but reduced the employment of less-educated young men. A panel analysis based on matched Labor Force Survey data indicates that the minimum-wage hike decreased the job flows of prime-age men and women.
Keywords: J23; J38; J42; J64; J81; 330; minimum wage; low skill workers; employment; Japan